Adaptasi Sosial Budaya Siswa Asal Papua - Dwiana Pujiasih (Jurnal Sosial Soedirman, 2019)
ABSTRACT Senior High School 3 Purwokerto is one of high school in Purwokerto which is appointed by the government to hold ADEM program to facilitate student from Papua. The problem appears when the student from Papua has to move and leave their culture to join Javanese culture which is a huge diffrent compare to their culture. This will cost a not easy way to deal with their new culture in their new environment until their project completed. The process of adaptation is interested to be discussed. This research is aimed to find out the way how Papua’s student deal with their new environment during their project and they finish it in Senior High School 3 Purwokerto. This research is done by using qualitative method with the subject of research is Student of Senior High School 3 Purwokerto. The process of obtaining sample is done by doing observation deep interview. The result of the study show that all subject research were in trouble with social culture adaptation, however they keep overcoming those troubles by making various adaptation strategic.